Analysis Of Export Competitiveness Indonesian Patchouli Produce In The International Market : RCA And ISP Approaches - Adiwijaya, Wan Adiwijaya; Siti Sabrina Salqaura (The Manager Review, 2025)
Global demand for patchouli oil reaches around 1,500 tonnes annually, with Indonesia supplying around 70 per cent of total demand. The area under patchouli cultivation in Indonesia has declined by an average of 1.52 per cent per year, and patchouli production in 2024 is estimated to reach only 2,220 tonnes, a sharp decline of 14.17% compared to the 2023 figure. However, the price of patchouli at the farmer level in the domestic market is quite encouraging. Therefore, with the increase in patchouli prices, farmers are expected to be able to increase production and exports of patchouli products in the international market. Indonesia's patchouli export destinations are spread across the continents of Asia, Europe, and Africa. The researcher aims to analyse coffee exports (HS 0901) to the largest export destinations, namely Egypt, Malaysia, Italy, and Japan, although in this case, coffee export volumes have decreased. This study is a secondary data analysis using time series data from 2014 to 2023. The export data analysed pertains to clove exports with HS code 3301 to Vietnam, Thailand, the Philippines, Singapore, and France, using Revealed Comparative Advantage Analysis and the Trade Specialisation Index. Based on the results of the Revealed Comparative Advantage (RCA) and Trade Specialisation Index (ISP) analyses, it can be concluded that Indonesian patchouli products have a very strong competitive position in the international market. The RCA values for several major export destinations, particularly Singapore, the Philippines, and Vietnam, indicate consistent comparative advantages.